The potential protective effect of ovothiol-a on high-fat diet-induced obesity in Rats - Nada Hussien Arafa Mahmoud; Mohamed Refaat; Ayman Saber (2024)
Background: Obesity is a serious chronic metabolic disease impairing health damaging various organs, such as the liver, kidneys, and skeletal muscles. Ovothiol-A (Ovo-A) is found to maintain the redox balance normal in sea urchins (Paracentrotus lividus), demonstrating its antioxidant characteristics. Aim: Investigation of the protective effect of Ovo-A on the liver, kidneys, and skeletal muscles in obese rats. Methods: In-Silico studies were performed on lactate dehydrogenase (LDH) and creatine kinase (CK) with Ovo-A to compute their binding affinities. Obesity was induced by utilizing a high-fat diet (HFD) for 4 weeks. Wistar rats were used in this study, 6 rats per group, as Control, HFD, Ovo-A (200 and 400 mg/Kg, p.o) groups. Results: Docking results have revealed that Ovo-A has affinities to bind to LDH (-8.5 kcal/mol) and CK (-17.7 kcal/mol). Ovo-A reduced the levels of glucose, insulin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), uric acid, urea, creatinine, LDH, CK, malondialdehyde (MDA), and nitric Oxide (NO); while increasing the levels of albumin (Alb), total protein (TP), high-density lipoprotein cholesterol (HDL-C), glutathione (GSH), catalase (CAT), and glutathione-S-transferase (GST). Histopathological investigations have revealed that Ovo-A restored the hepatic, renal, and muscular structures. Conclusion: The current study demonstrated that Ovo-A has a protective effect on the liver, kidneys, and skeletal muscles in obese rats. Ovo-A improves the antioxidant system while enhancing renal and muscular functions by inhibiting LDH and CK activities. Ovo-A is more effective in the high-dose.
(3GdfXQI GdYGeI(B: (3GdSefI gj eQV CjVj eRef NWjQ jVYa GdUMI hjdMb GdVQQ HGdYOjO ef GdCYVGA eKd GdcHO hGdcdi hGdYVdGJ GdgjcdjI(B. (3Je GdYKhQ Ydi CahKHhd C (B(Ovo-A) (3ddMaGX Ydi JhGRf GdCcSOI hGdGNJRGd GdWHjYj aj bfGaP GdHMQ eeG jTjQ Edi NUGFUg GdeVGOI ddCcSOI(B. (3GdgOa(B: (3OQGSI GdJCKjQ GdhbGFj d` (BOvo-A (3Ydi GdcHO hGdcdi hGdYVdGJ GdgjcdjI aj GdLQPGf GdSejfI(B. (3GdefgLjI(B: (3Je ELQGA OQGSGJ MGSHjI Ydi GdGcfJjO GdOjgjOQhLjfj (B(LDH) (3hcQjGJjf cjfGR (B(CK) (3eY (BOvo-A (3dMSGH bGHdjI GdGQJHGW Hjfge(B. (3oCSJMKJ GdSefI YHQ GJHGY fXGe ZPGFj YGdj GdOghf (B(HFD) (3deOI (B4 (3CSGHjY(B. (3Je GSJNOGe aFQGf (BWistar (3aj gPg GdOQGSI HhGbY (B6 (3aFQGf dcd eLehYI ef GdJGdj(B: (3eLehYI GdJMce, eLehYI Gd`(BHFD (3, heLehYJG Gd`(BOvo-A (200 (3h (B400 (3edj Le(B/(3cLe (Bp.o). (3GdfJGFL(B: (3cTaJ fJGFL GdMGSHjI Cf (BOvo-A (3jbOQ Gf jQJHW H` (BLDH (-8.5 (3cjdh cGdhQj(B/(3ehd(B) (3h(BCK (-17.7 (3cjdh cGdhQj(B/(3ehd(B). (3ojNpaV (BOvo-A (3eSJhjGJ GdLdhchR hGdCfShdjf hCdGfjf GdCejfhJQGfSajQjR (B(ALT) (3hCSHGQJGJ GdCejfhJQGfSajQjR (B(AST) (3hGdLGeGLdhJGejd JQGfSajQGR (B(GGT) (3hGdCdcGdjf ahSaGJjR (B(ALP) (3hGdchdjSJQhd Gdocdj (B(TC) (3hGdOghf GdKdGKjI (B(TG) (3hchdjSJQhd GdHQhJjf GdOgfj efNaV GdcKGaI (B(LDL-C) (3hMeV GdjhQjc hGdjhQjG hGdcQjGJjfjf h(BLDH (3h(BCK (3hGdeGdhfOjGdOgjO (B(MDA) (3hCcSjO GdfjJQjc (B(NO) (3eY RjGOI eSJhjGJ GdCdHhejf (B(Alb) (3hGdHQhJjf Gdcdj (B(TP) (3hchdjSJQhd GdHQhJjf GdOgfj YGdj GdcKGaI (B(HDL-C) (3hGdLdhJGKjhf (B(GSH) (3hGddGcJjR (B(CAT) (3hGdLdhJGKjhf(B-S-(3JQGfSajQGR (B(GST). (3CXgQJ GdfJGFL GdfSjLjI Cf (BOvo-A (3CUdM GdHfjI GdcHOjI hGdcdhjI hGdYVdjI ddYVdGJ GdgjcdjI(B. (3GdGSJfJGLGJ(B: (3CXgQJ GdOQGSI GdMGdjI Cf (BOvo-A (3dg JCKjQ hbGFj Ydi GdcHO hGdcdi hGdYVdGJ GdgjcdjI aj GdLQPGf GdSejfI(B. (3jYRR (BOvo-A (3hXGFa Gdcdi hGdYVd Gdgjcdj Yf WQjb JKHjW CfTWI (BLDH (3h(BCK (3hJMSjf fXGe eVGOGJ GdCcSOI(B. (3cGf (BOvo-A (3CcKQ aYGdjI aj GdLQYI GdYGdjI(B.s
Thesis (M.Sc)-Cairo University, 2024.
Bibliography: pages 50-67.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Biotechnology; Ovothiol-A -- Obesity -- High-Fat Diet -- Oxidative Stress -- Liver -- Kidney -- Skeletal Muscles